Reformulasi Perlindungan Hukum terhadap Polri dalam Penanganan Demonstrasi Anarkis - Eko Hendrawan; Made Warka; Moh Zeinudin (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Managing violent protests in Indonesia is a complex challenge for the Indonesian National Police (Polri): ensuring public order while safeguarding citizens' rights to free expression. The current legal framework is insufficiently clear to offer appropriate legal protection for Polri personnel operating in emergency and high-risk scenarios. This elevates the danger of criminal liability for the discretionary use of force by Polri officers. This study seeks to examine the legal protections available to Polri officers in managing violent demonstrations and to provide an improved legislative framework that addresses the operational requirements of the police force. This study uses a normative legal methodology to examine rules, judicial rulings, international standards, and pertinent examples. The results show that legal protection is still partial and not specific. A reformulation of legal protection is necessary, emphasizing three aspects: first, the establishment of more specific and clear regulations, including updated standard operating procedures, discretionary protection clauses, and guidance on the principle of proportionality grounded in law; second, the implementation of an internal legal support mechanism for Polri members; and third, the enhancement of accountability that consistently safeguards Polri members.